Effect of dexmedetomidine in children undergoing general anesthesia with sevoflurane: a meta-analysis - Marco Aurélio Soares Amorim (Revista Brasileira de Anestesiologia)
Abstract Background and objectives: Sevoflurane is often used in pediatric anesthesia and is associated with high incidence of psychomotor agitation. In such cases, dexmedetomidine (DEX) has been used, but its benefit and implications remain uncertain. We assessed the effects of DEX on agitation in children undergoing general anesthesia with sevoflurane. Method: Meta-analysis of randomized clinical and double-blind studies, with children undergoing elective procedures under general anesthesia with sevoflurane, using DEX or placebo. We sought articles in English in PubMed database using the following terms: Dexmedetomidine, sevoflurane (Methyl Ethers/sevoflurante), and agitation (Psychomotor Agitation). Duplicate articles with children who received premedication and used active control were excluded. It was adopted random effects model with DerSimonian-Laird testing and odds ratio (OR) calculation for dichotomous variables, and standardized mean difference for continuous variables, with their respective 95% confidence interval (CI). Results: Of 146 studies identified, 10 were selected totaling 558 patients (282 in DEX group and 276 controls). The use of DEX was considered a protective factor for psychomotor agitation (OR = 0.17; 95% CI 0.13-0.23; p < 0.0001) and nausea and vomiting in PACU (OR = 0.49; 95% CI 0.35-0.68; p < 0.0001). Wake-up time and PACU discharge time were higher in the dexmedetomidine group. There was no difference between groups for extubation time and duration of anesthesia. Conclusion: Dexmedetomidine reduces psychomotor agitation during wake-up time of children undergoing general anesthesia with sevoflurane.